Seasonal changes of small-scale polygons near the Martian south pole - van Gasselt, S.; Reiss, D.; Neukum, G. (2004)
North and south of 30°N/S latitude a belt of ~40° with morphologies resembling terrestrial analogues in periglacial environments can be observed in high resolution imagery of the Mars Orbiter Camera. Among them, the small–scale polygonal features have a striking resemblance with ice–wedge polygons in terrestrial permafrost regions. Nevertheless, their formation could not be unambiguously attributed to thermal contraction only and formation by e.g. desiccation has been proposed alternatively. The fresh appearance of polygon troughs, the low relief, seasonal CO2 frost infill as well as the absence of impact craters on the surface imply a recent formation and recent changes in their morphology. Seasonal observations near the south pole show a pattern of fissures in two subsequent Martian years which show major differences in their crack pattern. These data suggest thermal contraction cracking within a seasonal uppermost layer. The reactivation of older crack patterns and the development of higher–degree–racks as seen on Earth seem to be of minor importance. This observation strongly discourages the idea of subsurface ice wedges underneath these prominent fissure networks in several regions of the southern pole and might be due to seasonal surficial thermal contraction only. Below ~75°S the stability of liquid water and therefore thawing of the upper layer, is still questionable and modeling has been performed on a large scale only (Haberle et al., JGR, 2001). However, local thawing processes cannot be ruled out completely within troughs or in the vicinity of dunes, where temperatures and pressures my reach required values for thawing within the active layer. Still thermal contraction processes based on CO2 could be an alternative without analogues in terrestrial earth sciences.